A Simulation of the Reception of Automatic Dependent Surveillance-Broadcast Signals in Low Earth Orbit. (23rd August 2015) - Van Der Pryt, Richard; Vincent, Ron
Abstract : Automatic Dependent Surveillance-Broadcast (ADS-B) is an air traffic surveillance technology in which aircraft transmit position and identification. The development of space-based ADS-B will allow precise control of aircraft in areas that are not covered by radar, such as oceanic regions and high latitudes. The Royal Military College of Canada has developed a spaceborne ADS-B receiver scheduled to fly on the Canadian Advanced Nanospace eXperiment-7 (CanX-7) satellite. The payload is planned to collect data over the North Atlantic region, which will then be compared to truth data provided by air traffic services. A model was created to determine power levels arriving at the satellite to provide confidence in the ADS-B receiver and antenna proposed for CanX-7. The model takes into account neutral atmosphere and ionospheric effects, aircraft-satellite geometry, and antenna radiation patterns. A simulation was run by inserting real aircraft data from the North Atlantic Track System into the model and placing the satellite at altitudes of 400, 600, and 800 km. Results of the simulation indicate that power received at the satellite, ranging between −98.5 dBm and −103 dBm for the selected altitudes, will be sufficient to successfully conduct the mission.